2017
DOI: 10.7717/peerj.3222
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral response of prey fish to predators: the role of predator size

Abstract: Predation is one of the key factors governing patterns in natural systems, and adjustments of prey behaviors in response to a predator stimulus can have important ecological implications for wild fish. To investigate the effects of predators on the behavior of prey fish and to test whether the possible effects varied with predator size, black carp (Mylopharyngodon piceus) and snakehead (Channa argus) (a size-matched predator treatment with a similar body size to prey fish and a larger predator treatment with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Prey species can use some characteristics of their predators to evaluate predation risk: body size, eye position and eye-gaze, olfactory cues and sounds cues (Carter et al 2008;Hettena et al 2014, Schmitz 2017Tang et al 2017). For example, the larger the predator, the greater the risk of predation (Cohen et al 1993;Preisser & Orrock 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prey species can use some characteristics of their predators to evaluate predation risk: body size, eye position and eye-gaze, olfactory cues and sounds cues (Carter et al 2008;Hettena et al 2014, Schmitz 2017Tang et al 2017). For example, the larger the predator, the greater the risk of predation (Cohen et al 1993;Preisser & Orrock 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While our study is limited to laboratory studies, from an ecological perspective, evidence of SIH in fish may raise questions. Many studies have shown that a common behavioural response to the presence of predators in fish is reduced swimming activity and/or lowered metabolism (Kopack et al, 2015;Tang et al, 2017). Moving to warmer areas in response to a stressor, as is required to exhibit SIH, would be at odds with this anti-predator response in many fish.…”
Section: Discussionmentioning
confidence: 99%
“…The trajectory of each frame was digitized with the idTracker software (Pérez-Escudero et al, 2014; Tang et al, 2017), which automatically tracked the position of each fish in each trial and provided all x and y coordinates for each fish in each video (Miller & Gerlai, 2012; Killen et al, 2016). When the fish were measured in the group, only the data from the focus fish were recorded and analyzed.…”
Section: Methodsmentioning
confidence: 99%